Exploring shifts in values among urban Senegalese: The impact of global crises on social and cultural norms - Yachiyo Tobita; Mandiaye Diagne; Joseph Bassama; Moussa Ndong; Mor Gueye; Kiyokazu Ujiie (PLoS ONE, 2025)
The COVID-19 pandemic triggered social and economic stagnation worldwide, significantly impacting people’s lives. In addition, the Russia-Ukraine war that began in 2022 resulted in rising food prices globally, severely affecting low- and middle-income countries. This study aimed to examine the impact of these unprecedented crises on individual values, focusing on Senegal’s urban population. This study is the first to quantitatively assess changes in the values of urban Senegalese during this global crisis. Surveys were conducted in Saint-Louis, Senegal, in August-September 2018 and June-July 2022. The timing of these studies coincides with the onset of the COVID-19 pandemic in early 2020 and the outbreak of the Russia-Ukraine war in February 2022. The findings revealed a 19.9% decrease in the average monthly cost of living per capita between 2018 and 2022, attributed to the combined effects of rising food prices and unemployment. Furthermore, the proportion of households spending less than $3.50 per person per day—below the lower-middle-income class poverty line—increased by 11.05%. Our analysis indicates a decline in values such as benevolence, universalism, hedonism, and self-direction. In contrast, values related to power and achievement significantly increased following the pandemic. These results suggest that individual values are flexible and may change in response to external factors such as global crises.